Proactive Personality and Support: Buffering Job Insecurity’s Effect on Satisfaction - Ramadhan, Naufal Wahyu; Wulandari, Siti Zulaikha; Indyastuti, Devani Laksmi (Dinasti Publisher, 2025)
The purpose of this research is to analyse the relationship between private sector non-permanent workers' levels of job satisfaction and their levels of job insecurity in Banyumas Regency. It focusses on the ways in which proactive personality traits and the perception of organisational support mediate this connection. Data were obtained from 100 respondents using a quantitative survey approach and analysed using Partial Least Squares via SmartPLS 4. Work instability is associated with lower levels of work satisfaction, according to the research. Although it shown a favourable tendency, proactive personality did not considerably attenuate this negative association. On the other hand, work satisfaction was less affected by job insecurity when perceived organisational support acted as a moderator. In light of these results, it is clear that employees' well-being in conditions of job uncertainty is best maintained via the use of external support systems. Internal psychological qualities and perceived organisational elements as modifiers are also included in the research, which adds to the literature. This is especially true in the context of contract-based employment in Indonesia. This research underlines the need for companies to foster supportive environments and pay attention to psychological conditions that may impact satisfaction and productivity, especially among non-permanent employees.